The Compatibility between leadership of empowerment and organizational learning abilities and their reflection on knowledge capital Applied research at Wasit University - الملا عبد الرحمن مصطفى; عباس قاسم حبوب (Journal of Economics and Administrative Sciences, 2019)
The current research aims at: - Identifying the role played by the leadership in empowerment and organizational learning abilities and their reflection on the knowledge capital, and the extent to which these concepts can be applied effectively at Wasit University. The problem of research .... In a series of questions: The most important is that the dimensions leadership empowerment and distance learning organizational capacity correlation relationship and impact and significant statistical significance with the capital knowledge. To understand the nature of the relationship and the impact between the variables, leadership was adopted by empowerment as the first explanatory variable of four dimensions (enhancing the meaning of work, expressing confidence in high performance, providing independence from bureaucratic constraints, participation in decision-making), organizational learning capabilities as a second explanatory variable (Experimentation and openness, sharing and transfer of knowledge, dialogue and interaction with the external environment), knowledge capital as a four-dimensional variable (human capital, structural capital, client capital, operational capital) (63) respondents, which targeted the heads of the departments of the University of Wasit in Wasit, starting from a number of hypotheses, the most important of which is: There is a significant multi-significance effect of leadership in empowerment and organizational learning abilities in a society. The data were analyzed and the hypotheses were tested using appropriate statistical tools and analyzed through a number of ready statistical programs (SPSS, ver 19). The results of the research reached a number of conclusions, the most important of which were: The study recommended a set of recommendations, the most important of which enhancing the knowledge capital in the university and its positive impact on the general performance of the university